Global Health Education in UK Medical Schools (GHEMS) study protocol - Soham Bandyopadhyay; Thomas Shortland; Shavinthi W Wadanamby; Hannah S Thomas; Binay Gurung; Melika Akhbari; Isobel Trout; Rashida Patel; Karisma Sharma; J Edward Fitzgerald; Adrian D Smith (Journal of Global Health Reports)
# Background